KEKERASAN DALAM PACARAN:FENOMENA LINGKARAN SETAN HUBUNGAN BERACUN DENGAN SIKAP MATERIALISME - Agnes Beatrix Jackline Raintung; Kahimpong, Monika; Atalya Deharda Paraeng; Bless Makapedua; Debora Natalia Horohiung; Deeker Sumolang; Incha kasalang; Jenifer Theresia Paulus; Meilani Dalending; Norlanda Darondo; Yolanda Lokong (PT. Giat Konseling Nusantara, 2024)
Violence in dating is something that is increasingly worrying, where relationships that should be based on love and mutual understanding turn into a vicious, toxic circle. This article aims to examine violence in dating by highlighting materialism as a factor that has an influence on violence in dating. Through a descriptive qualitative approach, this research identifies how materialism can influence power dynamics in relationships, increase conflict, and exacerbate violence. Materialism often creates incompatible desires and economic pressures that can trigger aggressive and manipulative behavior. It is hoped that this research can help victims to seek help, and encourage the formation of healthy relationships free from violence.